2021
DOI: 10.1007/s13238-021-00858-3
|View full text |Cite|
|
Sign up to set email alerts
|

Metformin activates chaperone-mediated autophagy and improves disease pathologies in an Alzheimer disease mouse model

Abstract: Chaperone-mediated autophagy (CMA) is a lysosome-dependent selective degradation pathway implicated in the pathogenesis of cancer and neurodegenerative diseases. However, the mechanisms that regulate CMA are not fully understood. Here, using unbiased drug screening approaches, we discover Metformin, a drug that is commonly the first medication prescribed for type 2 diabetes, can induce CMA. We delineate the mechanism of CMA induction by Metformin to be via activation of TAK1-IKKα/β signaling that leads to phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
58
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 66 publications
(56 reference statements)
2
58
0
Order By: Relevance
“…Besides, chaperone-mediated autophagy (CMA), a lysosome-dependent selective degradation pathway, was also implicated in DNA methylation ( Dice, 2007 ). CMA was reported to be suppressed at an early stage of AD and its activation could reduce the levels of Aβ plaques and tau phosphorylation, and ameliorate behavioral phenotype ( Dou et al, 2020 ; Bourdenx et al, 2021 ; Xu X. et al, 2021 ; Caballero et al, 2021 ). These evidences support an unequivocal role for CMA in the development of AD.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, chaperone-mediated autophagy (CMA), a lysosome-dependent selective degradation pathway, was also implicated in DNA methylation ( Dice, 2007 ). CMA was reported to be suppressed at an early stage of AD and its activation could reduce the levels of Aβ plaques and tau phosphorylation, and ameliorate behavioral phenotype ( Dou et al, 2020 ; Bourdenx et al, 2021 ; Xu X. et al, 2021 ; Caballero et al, 2021 ). These evidences support an unequivocal role for CMA in the development of AD.…”
Section: Discussionmentioning
confidence: 99%
“…Is it the structure of the receptor that determines this process and is there a propensity to degrade the damaged protein under certain conditions? In one recent study, APP protein was found to be the receptor of CMA [ 240 ], and APP could conduct both macroautophagy and CMA. However, how to conduct macroautophagy and CMA, and whether there is a priority between the two are problems to be solved in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, LAMP2A overexpression attenuates neurodegeneration in cellular and animal models of Parkinson’s disease [ 46 ]. Moreover, the chemicals that activate CMA have therapeutic effects in cellular and animal models of Alzheimer’s disease [ 44 , 47 ]. These findings suggest that CMA can be a potential target for the treatment of various neurodegenerative diseases, including SCA, Parkinson’s disease, and Alzheimer’s disease.…”
Section: Discussionmentioning
confidence: 99%